Analisis Pengaruh Suku Bunga, Harga Minyak Dunia, Harga Emas Dunia Terhadap Indeks Harga Saham Gabungan Dengan Inflasi Sebagai Variabel Moderating Di Indonesia - A. Mahendra; Mekar Meilisa Amalia; Hengky Leon (Owner : Riset dan Jurnal Akuntansi, 2022)
This research is intended to know the influence of interest rate, world oil price, and world gold price on joint stock price index with inflation as a moderating variables in Indonesia. Population in this research is Indonesia and 20 of them were selected to be the samples for this research through purposive sampling technique. Estimates conducted by the multiple regression analysis. The data that were used in this study were secondary data, consisted of Interest Rate, World Oil Price, and World Gold Price to Joint Stock Price Index for the year 2000-2019. The results of this research, that Based on the partial test (t test), the Interest Rate variable has no significant effect while the World Oil Price and World Gold Price have a significant effect on the variables of the Joint Stock Price Index in Indonesia, the simultan test (F test), Interest Rate, World Oil Price and World Gold Price have a significant effect on the variables of the Joint Stock Price Index. The inflation are unable to moderate the relationship between interest rate, world oil price and world gold price on the joint stock price index.